Implementing High Energy Liquid Nutrition, Omega-3 Fatty Acids and Nutritional Supplements for the Treatment of Anorexia Nervosa - Christoph, Baumann; Christian, Willaschek; Tuende, Kertess-Szlaninka; Lang, Johanna; Reiner, Buchhorn (Journal of Pediatric Health And Nutrition, 2017)
Objective: To assess the effect of different treatment approaches on the course of anorexia nervosa (AN) over time. Methods: The subjects were 27 hospitalized AN patients. In our retrospective analysis we compared weight gain in two groups. While one group was treated with a standard oral refeeding protocol (historical control) through January 2013 (N=16), the second group (highly standardized refeeding protocol) received a high energy liquid nutrition and nutritional supplements including omega-3 fatty acids (N=11). Results: On admission, the two groups were comparable in terms of height, weight, age and heart rate. At the end of our monitoring time frame of 25 days, weight gain was 121.4% higher in the highly standardized refeeding protocol group than in the historical control group (66.5 ±52.4 vs 147.3 ±55.7 grams/day; t-Test p=0.004; CI95%: 29.3-132.2). A carbohydrate rich diet clearly improved weight gain if high energy liquid nutrition was replaced by the diet according the patient’s own wishes. About 45% of our patients stated they were vegetarians at admission. However, we could not identify a vegetarian diet as a statistically significant negative prognostic factor for weight gain. Conclusion: The highly standardized refeeding protocol seems to be helpful in malnourished AN patients to improve weight gain without enhancing the risk of a refeeding syndrome. However, further studies with greater number of patients are needed to confirm the effectiveness of our standardized treatment protocol.
Keywords: Anorexia nervosa; Eating disorders; Refeeding; omega-3-fatty acids